Pengembangan Ensiklopedia Tumbuhan Obat Etnis Melayu Berbasis Literasi Sains di Kawasan Pesisir Timur Sumatra Utara sebagai Sumber BelajarMata Kuliah Etnobotani - Rahmat Fajrin; Ashar Hasairin; Diky Setya Diningrat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop a scientific literacy-based ethnobotanical encyclopedia of medicinal plants of the Malay ethnic group in the Eastern Coastal region of North Sumatra and to determine the quality of the developed encyclopedia based on expert validation and user trials. The method used was Research and Development (R&D) adopting the ADDIE development model. Research instruments included validation sheets from material experts, instructional design experts, and layout design experts, as well as response questionnaires from ethnobotany course lecturers and students. The results showed that the developed encyclopedia received a validation score of 96.25% from instructional design experts, 89.7% from material experts, and 98.75% from layout design experts, all categorized as very valid. Lecturers’ responses indicated a practicality level of 89.73%, while student responses reached 94.23%, both categorized as very practical. In conclusion, the scientific literacy-based encyclopedia of Malay ethnic medicinal plants is valid and practical to be used as a learning resource in the Ethnobotany course. Keywords: ADDIE, encyclopedia, Malay ethnic group, medicinal plants, scientific literacy